Layered metal–organic framework/graphene nanoarchitectures for organic photosynthesis under visible light. Issue 48 (13th November 2015) - Xu, Jie; He, Sha; Zhang, Hualei; Huang, Jiancai; Lin, Huaxiang; Wang, Xuxu; Long, Jinlin
Abstract : By employing a noncovalent methodology, hierarchical rGO/MOF hybrids were successfully fabricated to enhance the photocatalytic performance for organic photosynthesis under visible light. Abstract : A layered nanoarchitecture composed of photoactive MOFs of UiO-66-NH2 and graphene was facilely fabricated herein by an innovative strategy, which utilizes a noncovalent methodology for graphene functionalization combined with in situ self-assembling and a solvothermal synthesis technique. The fabricated hybrids were characterized and evaluated in detail by the selective photocatalytic oxidation of benzyl alcohol under visible light. The hybrid displayed improved efficiency with high selectivity, compared with the parent MOF. The characterization results clearly demonstrate that this originates from the sandwich-like hierarchical nanoarchitecture formed by the compact interaction between UiO-66-NH2 and graphene via the adopted mediator. The synthesis strategy was also proven effective in building the rGO/NH2 -MIL-125(Ti) hierarchical nanoarchitecture. Thus, this work offers a general strategy for constructing MOF/graphene sandwich heterostructures, which have great potential in the fields of electronics, optics, optoelectronics, and photoconversion.